IMPLEMENTASI METODE COOPERATIF LEARNING TIPE JIGSAW PADA MATA PELAJARAN MATEMATIKA GUNA MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD N WAWASAN - Marilin Kristina Ponidi (Universitas Muhammadiyah Kotabumi, 2018)
Based on the results by preliminary observation about the low outcomes of grade V SDN Wawasan, the authors conducted a classroom action research to improve student learning outcomes. Collaborated with co-authors, writer tried to used Cooperative Learning Jigsaw Type in the first cycle learning, the second cycle, and the third cycle to improve class V student achievement on SDN Wawasan. Improvement plan through this research was found using Jigsaw Cooperative learning model to improve student learning outcomes. From the evaluation results can be seen the increment in the percentage of student learning outcomes that can achieve minimum completeness criterion (KKM) obtained in the first cycle is 30.65%, increased in the second cycle to 60%, and 90% in the third cycle. Thus the author need to master and use various models of learning in every learning activity in the school.